ATRT-03. Adapted Treatment Protocol: Synchronous Atypical Teratoid/Rhabdoid CNS Tumor and Extra CNS Disease. (3rd June 2022) - Jackson, Nicole; Torres, Marleni; Lecea, Eva Glenn; O'Farrell, Candelaria; Khatib, Ziad; Maher, Ossama
Abstract: Atypical teratoid/rhabdoid tumors (AT/RTs) of the central nervous system (CNS) are rare, aggressive, early childhood tumors with unfavorable prognosis. There have been 31 cases reported of children with AT/RT of the CNS and extra CNS primary tumors. In addition to its aggressive tendencies, malignant rhabdoid tumors (MRTs) of the kidney have also shown a common genetic abnormality-inactivating mutation of SMARC B1/INI-gene. We report a 22-month-old male who presented at 15 months of age with metastatic AT/RT of the posterior fossa and synchronous malignant rhabdoid tumor of the left kidney. MRI of the brain demonstrated a midline posterior fossa mass and left renal mass was noted incidentally on imaging of spine. Pathology was consistent with MRT of the kidney and pathogenic variant was found in the tumor sample, specifically SMARCB1 homozygous/biallelic deletion. Patient underwent a subtotal resection of the posterior fossa tumor and subsequent radical resection of the mass on kidney rhabdoid tumor. He was treated as per ACNS033 protocol with 2 cycles of induction with high-dose methotrexate followed by vincristine, cyclophosphamide, cisplatin, and etoposide with complete response followed by three tandem stem cell transplants with thiotepa and carboplatin for which he has been tolerating and responding favorably. Focal radiation therapy to the brain and flank area is planned at end of therapy. In a large series of synchronous AT/RTs reported in 2017 only 3 of the 31 patients were considered long-term survivors. All received a combination of high dose intrathecal or intravenous chemotherapy, total resection of at least one of the tumors, focal radiation, and autologous peripheral blood stem cell transplant. We demonstrated a case with a favorable response with our treatment. Treatment continues to be challenging given the tumor's rarity and mortality as there are no standardized protocols or randomized controlled trials.